Longitudinal observational study of sporadic inclusion body myositis: implications for clinical trials. - Cortese, A; Machado, P; Morrow, J; Dewar, L; Hiscock, A; Miller, A; Brady, S; Hilton-Jones, D; Parton, M; Hanna, MG (2013)
Sporadic inclusion body myositis (IBM) is the most common acquired myopathy occurring in adults aged over 50 years. The aim of the study was to assess prospectively the clinical features and functional impact of sporadic inclusion body myositis (IBM). Clinical data, manual muscle testing (MMT), quantitative muscle testing (QMT) of quadriceps muscle and IBM functional rating scale (IBM-FRS) were collected according to a standardised protocol at baseline (n=51) and one-year follow-up (n=23). MMT, quadriceps QMT and IBM-FRS significantly declined after one year (by 5.2%, 27.9%, and 13.8%, respectively). QMT of the quadriceps muscle and IBM-FRS were the most sensitive measures of disease progression. After a median time of seven years of disease duration, 63% of patients had lost independent walking. Disease onset after 55 years of age, but not sex or treatment, is predictive of a shorter time to requirement of a walking stick. We detected no differences in disease presentation and progression between clinically and pathologically defined IBM patients. The study provides evidence that quadriceps QMT and IBM-FRS could prove helpful as outcome measures in future therapeutic trials in IBM.